2021
DOI: 10.3390/nu13124457
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Intake in Adults Diagnosed with Metabolic Syndrome: Using the Health Examinee (HEXA) Cohort

Abstract: Macronutrient intake is important in the prevention and management of metabolic syndrome (MetS). This study aimed to evaluate total energy and macronutrient intake of participants diagnosed with MetS at recruitment of the health examinees (HEXA) cohort, considering the plant and animal sources of each macronutrient. We included 130,423 participants aged 40–69 years for analysis. Odds ratios (OR) and 95% confidence intervals (CI) were estimated to evaluate the intake of macronutrients stratified by gender. Ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Furthermore, participants with MetS were found to have higher carbohydrate and free sugar intakes consistent with consuming more carbohydrate-rich, low-fiber foods and lower amounts of protein-rich foods. Previous studies of Korean and Iranian adults [aged 20-69 years] reported higher carbohydrate and lower protein intakes in individuals with MetS [63], and that higher carbohydrate intakes increased MetS risk [64]. In contrast, a lower carbohydrate intake in individuals with MetS was reported in older adults from the Balearic Islands [65].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, participants with MetS were found to have higher carbohydrate and free sugar intakes consistent with consuming more carbohydrate-rich, low-fiber foods and lower amounts of protein-rich foods. Previous studies of Korean and Iranian adults [aged 20-69 years] reported higher carbohydrate and lower protein intakes in individuals with MetS [63], and that higher carbohydrate intakes increased MetS risk [64]. In contrast, a lower carbohydrate intake in individuals with MetS was reported in older adults from the Balearic Islands [65].…”
Section: Discussionmentioning
confidence: 94%
“…In detail, a basic simulation was carried out varying EB in the following range: −1000, −500, 0, 500, 1000 kcal (Figure 5A), with standard percentage contributions of carbohydrate, protein, and lipid intake (50/20/30%), respectively, included in acceptable macronutrient distribution ranges (AMDR) [31]. The values of macronutrient intakes were calculated by converting their percentages into grams [32]; then, the total caloric intake was evaluated by inverting Equation (1). From the simulations, we can observe that an energy deficit of 500 kcal per day yielded an average weight loss of −0.4 ± 0.2 kg in a week, while an energy surplus of 500 kcal yielded an average weight gain of 0.77 ± 0.63 kg in a week, and that differences existed among users.…”
Section: Simulation Of the Personalized Effects Of Diet Plans On Weightmentioning
confidence: 99%
“…MetS can be affected by age, sex, metabolism, genetics, and environmental factors, such as drinking, smoking, diet, and physical inactivity [ 17 , 18 ]. Diet and dietary patterns are important with respect to the development and management of MetS and its risk factors [ 19 , 20 , 21 , 22 , 23 ]. Dietary quality and patterns have been associated with MetS [ 24 ].…”
Section: Introductionmentioning
confidence: 99%